An Investigation of In Situ Cognitions of English Premier League Academy Football Coaches Using Stimulated Recall and Think Aloud Protocol - Max Chapman; Simon Nicholas Quick; Paul Freeman (CV. FOUNDAE, 2024)
Coaches must practice and mentally operate in complex social environments. However, research that has explored the mental processes of coaching is limited and has tended to employ singular methods. The purpose of this study is twofold. First, to understand what and how coaches think by combining two established knowledge elicitation. Think Aloud Protocol (TAP) and Stimulated Recall (SR). The two methods, working in conjunction, complement one another and cater to each other's shortcomings. Second, to examine the effectiveness of combining methods for the coach development sphere. This study used six English Premier League academy male football coaches who participated in both 'live' and 'retrospective' methods. For aim 1, a reflexive thematic analysis of the transcripts of the two combined methods resulted in developing two primary themes: Session management and noticing. These themes are populated with content to illustrate the subject of the coaches' thoughts. For aim 2, a reflexive thematic analysis of the coaches' reflexive interviews regarding their experiences of the methods displays the issues presented with each isolation method. Finally, the study reports on the effectiveness and possible deployment of the new method, which we propose as TAPSR and possible future applications for various stakeholders in the coach development realm. The novelty of this work has potential application to the applied world of sports coaching and contributes to the development of a more sophisticated knowledge elicitation method.